Flavor and aroma of low-dose irradiated, boneless, pork chops - S E Luchsinger; Zepeda C.M. Garcia; Edgar IV Chambers; M E Hollingsworth; Melvin C Hunt; James L Marsden; Sally L Stroda; Canas E Rubio J; Curtis L Kastner; W G Kuecker; T Mata; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1995)
Irradiation and irradiation source had little to no effect on flavor and aroma of boneless pork chops, either frozen or chilled. Coupled with consumer concerns about food safety and well-documented improvement in consumer attitudes about irradiated foods, irradiation of boneless pork chops has promising potential for market acceptance.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Irradiation; Flavor; Aroma